Characterization of lardo from Cinta Senese pigs: differences between seasoning techniques and starch sources - Sirtori F.; Pugliese C.; Bozzi R.; Campodoni G.; Franci O. (5. International Symposium on the Mediterranean Pig, 2007)
The trial was carried out to investigate the effect of the fattening diet (maize vs barley) and the seasoning technique (dry vs Colonnata) on fatty acid composition of seasoned backfat (lardo) from Cinta Senese pigs. Forty pigs were fattened with maize (20) or barley as main feed. Backfat from right side was seasoned according to the Colonnata technique placing the backfat in a marble vessel for a period of six months. Backfat from the left side was seasoned following the dry technique, adding salt and pepper, and then cured for three months in controlled conditions. The following analysis were carried out on lardo : moisture, total lipids, fatty acids and malonaldehyde (MDA) content. Few differences were found between diets. Lardo obtained with the technique showed higher MUFA (45.5 vs 44.9%) and lower PUFA percentage (16.8 vs 17.6%) and MDA content dry (0.49 vs 0.60 mg/kg lard) than that obtained with the Colonnata.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)